ANALISIS PEMAHAMAN KONSEP TATA SURYA SISWA MELALUI PAPAN INTERAKTIF DIGITAL PADA PEMBELAJARAN IPA KELAS VI SD - Septiani, Faiza Salsa; Fitri, Sri Aidha; Putri, Wila Julia; Fitria, Yanti; Kharisma, Inggria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Science learning in Grade VI elementary school, which is still dominated by conventional methods such as the use of textbooks and verbal explanations, is considered inadequate in facilitating deep conceptual understanding. Therefore, this study aims to analyze students’ conceptual understanding of the solar system through the use of digital interactive boards in science learning. This research employs a descriptive qualitative approach using a literature study method, with data sources obtained from indexed scientific journals published between 2020 and 2025. The findings indicate that the use of digital interactive boards enhances student engagement, supports the visualization of abstract concepts, and promotes deeper conceptual understanding through direct interaction with learning materials. Furthermore, this medium aligns with the demands of 21st-century learning, which emphasize the integration of technology and student-centered instruction. It can be concluded that digital interactive boards are an effective learning medium for improving students’ conceptual understanding of the solar system and have significant implications for the development of technology-based science learning in elementary schools.